Single-molecule visualisation of DNA G-quadruplex formation in live cells - Di Antonio, Marco (Nat Chem, 2020)
Substantial evidence now exists to support that formation of DNA G-quadruplexes (G4s) can alter gene-expression. However, approaches that allow to probe G4s in living cells without perturbing their folding dynamics are required to understand their biological roles in greater detail. Herein, we report a G4-specific fluorescent probe (SiR-PyPDS) that enables single-molecule and real-time detection of individual G4 structures in living cells. Live-cell single-molecule fluorescence imaging of G4s was carried out under conditions that use low concentrations of SiR-PyPDS (20 nM) to provide informative measurements representative of the population of G4s in living cells, without globally perturbing G4 formation and dynamics. Single-molecule fluorescence imaging and time-dependent chemical trapping of unfolded G4s in living cells, revealed that G4s fluctuate between folded and unfolded states. We also demonstrated that G4-formation in live cells is cell-cycle dependent and disrupted by chemical inhibition of transcription and replication. Our observations provide robust evidence in support of dynamic G4-formation in living cells.